Gastric Point-of-Care Ultrasound in Acutely and Critically Ill Children (POCUS-ped): A Scoping Review - Valla, Frederic V.; Tume, Lyvonne N.; Jotterand Chaparro, Corinne; Arnold, Philip; Alrayashi, Walid; Morice, Claire; Nabialek, Tomasz; Rouchaud, Aymeric; Cercueil, Eloise; Bouvet, Lionel (Frontiers in Pediatrics, 2022)
Introduction Point-of-care ultrasound (POCUS) use is increasing in pediatric clinical settings. However, gastric POCUS is rarely used, despite its potential value in optimizing the diagnosis and management in several clinical scenarios (i.e., assessing gastric emptying and gastric volume/content, gastric foreign bodies, confirming nasogastric tube placement, and hypertrophic pyloric stenosis). This review aimed to assess how gastric POCUS may be used in acute and critically ill children. Materials and Methods An international expert group was established, composed of pediatricians, pediatric intensivists, anesthesiologists, radiologists, nurses, and a methodologist. A scoping review was conducted with an aim to describe the use of gastric POCUS in pediatrics in acute and critical care settings. A literature search was conducted in three databases, to identify studies published between 1998 and 2022. Abstracts and relevant full texts were screened for eligibility, and data were extracted, according to the JBI methodology (Johanna Briggs Institute). Results A total of 70 studies were included. Most studies (n = 47; 67%) were conducted to assess gastric emptying and gastric volume/contents. The studies assessed gastric volume, the impact of different feed types (breast milk, fortifiers, and thickeners) and feed administration modes on gastric emptying, and gastric volume/content prior to sedation or anesthesia or during surgery. Other studies described the use of gastric POCUS in foreign body ingestion (n = 6), nasogastric tube placement (n = 5), hypertrophic pyloric stenosis (n = 8), and gastric insufflation during mechanical ventilatory support (n = 4). POCUS was performed by neonatologists, anesthesiologists, emergency department physicians, and surgeons. Their learning curve was rapid, and the accuracy was high when compared to that of the ultrasound performed by radiologists (RADUS) or other gold standards (e.g., endoscopy, radiography, and MRI). No study conducted in critically ill children was found apart from that in neonatal intensive care in preterms. Discussion Gastric POCUS appears useful and reliable in a variety of pediatric clinical settings. It may help optimize induction in emergency sedation/anesthesia, diagnose foreign bodies and hypertrophic pyloric stenosis, and assist in confirming nasogastric tube placement, avoiding delays in obtaining confirmatory examinations (RADUS, x-rays, etc.) and reducing radiation exposure. It may be useful in pediatric intensive care but requires further investigation.